CROSS-MEDIA IN PUBLISHING: THE CASE OF DAILIES IN LITHUANIA - MISEVIČIŪTĖ, ADA (Knygotyra, 2011)
The cross-media publishing is an unexplored subject in media studies in Lithuania. The object of the study was cross-media publishing by dailies in Lithuania. The objective was to present cross-media and to assess their use by daily newspapers. The tasks were to do research on cross-media concept and definition, to analyse the development of cross-media and to study how cross-media products are created, to explore the reasons for making a decision to develop cross-media strategies in publishing houses and to present the upcoming challenges of such a choice, to investigate the use of cross-media by Lithuania’s dailies. In summary, it should be noted that the evolution of cross-media practices and a bigger integration in newspapers are related with the number of media used for creating a story. It should be perceived that each medium is equally important. The conclusion is made that more professional fitting of the content and a bigger amount of content migration between different media means a bigger integration. The number of cross-media journalists and a successful fight with cross-media challenges can be used to indicate the level of success in cross-media as well. Later on, the research was designed to investigate the use of cross-media in major Lithuanian dailies. To get the initial idea of the situation in using cross-media in Lithuanian dailies, an analysis of newspapers’ website content and document analysis was made. Then, considering the findings, the news editors were asked to answer the questionnaires about collaboration among different media. The data have shown that the biggest newspapers are practicing cross-media, and some are very well informed about newsroom convergence trends. The level of integration differs in different newspapers.